2017
DOI: 10.1530/ec-17-0129
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome and the risk of obstructive sleep apnea: a meta-analysis and review of the literature

Abstract: Background and ObjectivePolycystic ovary syndrome (PCOS) has been reported to be associated with the development of obstructive sleep apnea (OSA). The objective of this meta-analysis is to assess the relationship between PCOS and OSA.MethodsA literature search was conducted to identify studies linking PCOS with the risk of OSA. Studies in which the presence of OSA was confirmed with overnight polysomnography were included. Random effects models were used to calculate pooled relative risks.ResultsEight studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 44 publications
2
56
0
2
Order By: Relevance
“…28 Testosterone supplementation in men may increase the risk of OSA, 29 and OSA has been linked to polycystic ovary syndrome, a condition characterized by increased levels of endogenous testosterone. 30 Studies have shown women have higher minute ventilation at rest compared to men 31 and cyclic fluctuations in ventilation with menstrual cycle that stop with menopause. 32 In women, there is a rapid decline in estrogen and progesterone at menopause, while testosterone decreases gradually.…”
Section: Pathophysiological Factorsmentioning
confidence: 99%
“…28 Testosterone supplementation in men may increase the risk of OSA, 29 and OSA has been linked to polycystic ovary syndrome, a condition characterized by increased levels of endogenous testosterone. 30 Studies have shown women have higher minute ventilation at rest compared to men 31 and cyclic fluctuations in ventilation with menstrual cycle that stop with menopause. 32 In women, there is a rapid decline in estrogen and progesterone at menopause, while testosterone decreases gradually.…”
Section: Pathophysiological Factorsmentioning
confidence: 99%
“…However, the reported prevalence of OSA in women with PCOS has been very wide, ranging from 0 to 70% [17,37], which raises concerns about the methodologies used in these studies. Similarly, a recent meta-analysis has attempted to answer this question [38]; however, the review contained significant methodological weaknesses that question its validity ('OSA prevalence in PCOS' in discussion). To date, there is no comprehensive, well-conducted, systematic review that examined the prevalence of OSA in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our meta-analysis, OSA is present in almost onethird of women with PCOS. In the recent meta-analysis by Helvaci et al, the prevalence of OSA was lower at 0.22 (95% CI 0.08-0.40) in women with PCOS [38]. The lower OSA prevalence reported could be explained by differences in study methodology.…”
Section: Osa Prevalence In Pcosmentioning
confidence: 91%
“…However, the reported prevalence of OSA in women with PCOS has been very wide, ranging from 0 to 70% [17,37], which raises concerns about the methodologies used in these studies. Similarly, a recent meta-analysis has attempted to answer this question [38]; however, the review contained significant methodological weaknesses that question its validity ('OSA prevalence in PCOS' in discussion). To date, there is no comprehensive, well-conducted, systematic review that examined the prevalence of OSA in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%